A comparison between the neurocognitive profile of Huntington Disease-Like 2 and Huntington Disease: Exploring the presence of double dissociations. Issue 2 (4th March 2022) - Ferreira-Correia, Aline; Anderson, David G.; Cockcroft, Kate; Krause, Amanda
Abstract: Huntington Disease Like-2 (HDL2) is a rare autosomal dominant genetic disease caused by a mutation in the JPH3 gene. HDL2 is the Huntington Disease (HD) phenocopy that has the greatest clinical resemblance to HD. Both are characterized by movement, psychiatric and cognitive dysfunction, which progress to dementia. The present study compared the neuropsychological profile of HDL2 with that of HD. Using a Single Case-Control Methodology in Neuropsychology, three HDL2 and seven matched HD patients were assessed with a comprehensive neuropsychological battery and compared to matched control samples, considering age, years of education, type of school (public/government) and language (all bi/multilingual). Potential double dissociations were explored by using Crawford, Garthwaite, and Wood's Inferential Methods for Comparing the Scores of Two Single-Cases in Case-Control Designs. Double dissociation between HDL2 and HD were identified in three tests, namely Letter Number Sequencing, Rey Auditory Learning Test Delayed and Recognition Trials. These dissociations possible are due to methodological limitations.